2001
DOI: 10.1002/1615-4169(200107)343:5<379::aid-adsc379>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the Preparation of Enantiomerically Pure (2R,2′R)-(+)-threo-Methylphenidate Hydrochloride

Abstract: Various approaches to the preparation of enantiomerically pure (2R,2′R)‐(+)‐threo‐methylphenidate hydrochloride (1) are reviewed. These approaches include synthesis using enantiomerically pure precursors obtained by resolution, classical and enzyme‐based resolution approaches, enantioselective synthesis approaches, and approaches based on enantioselective synthesis of (2S,2′R)‐erythro‐methylphenidate followed by epimerization at the 2‐position. 1 Introduction 2 Methods for the Enhancement of Enantiomeric Purit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…52 The mean absolute bioavailability of dl-MPH has been reported to be 30%, but ranges from 11% to 51%. 60,61 In effect, first-pass metabolism biocatalytically "resolves" oral dl-MPH, 62 resulting in only the d-isomer appreciably reaching the bloodstream. The d-isomer component of dl-MPH is generally regarded as the pharmacologically active isomer, responsible for efficacy in the treatment of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…52 The mean absolute bioavailability of dl-MPH has been reported to be 30%, but ranges from 11% to 51%. 60,61 In effect, first-pass metabolism biocatalytically "resolves" oral dl-MPH, 62 resulting in only the d-isomer appreciably reaching the bloodstream. The d-isomer component of dl-MPH is generally regarded as the pharmacologically active isomer, responsible for efficacy in the treatment of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…3 The activity of Ritalin ® promotes an enhancement of the cognitive performance in both adults and children diagnosed with AD/HD. 4 Although Ritalin ® is available in the market as the racemate, the (2R,2%R)-(+)-threo-methylphenidate has been reported to be up to 38 times 5 more active than (2S,2%S)-(−)-threo-methylphenidate and several racemic [6][7][8][9] and chiral [10][11][12][13] synthesis of threo-methylphenidate were reported previously.…”
Section: Thementioning
confidence: 99%
“…In this way, a set of available tertiary amines as bases was investigated. In all cases a variable ratio of compounds 2 and 5 was observed ( Table 1, entries [8][9][10][11][12][13][14] and the use of KOt-Bu furnished the compound 5 as a major product (entry 15). Interestingly, the best yield of compound 2 (60%) was achieved when DBU was employed in the absence of a thiophile (Table 1, entry 14) in which thiazolidinone 5 was not isolated.…”
Section: Thementioning
confidence: 99%
“…[5,6] Originally, it was marketed as a mixture of two racemates, consisting of 80% (±)-erythro and 20% (±)-threo isomers, but successive studies demonstrated that the pharmacologically active diastereomers are associated with the (±)-threo form. [7][8][9][10] Subsequent studies focused on the separation of the two diastereomers and interconversion of (±)-erythro racemate to its (±)-threo counterpart. The (±)-threo racemate exists as two enantiomers, (+)-threo-MPH (2R,2'R) and (-)-threo-MPH (2S,2'S), and the absolute stereochemistry of the most pharmacologically active enantiomer of MPH ((+)-threo) has been characterized [11][12][13] and developed as a medication to treat ADHD in its own right.…”
Section: Introductionmentioning
confidence: 99%